2016
DOI: 10.1016/j.chom.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

An Intrinsically Disordered Region of the DNA Repair Protein Nbs1 Is a Species-Specific Barrier to Herpes Simplex Virus 1 in Primates

Abstract: Summary Humans occasionally transmit herpes simplex virus-1 (HSV-1) to captive primates, who reciprocally harbor alphaherpesviruses poised for zoonotic transmission to humans. To understand the basis for the species-specific restriction of HSV-1 in primates, we simulated what might happen during the cross-species transmission of HSV-1 and found that the DNA repair protein Nbs1 from only some primate species are able to promote HSV-1 infection. The Nbs1 homologs that promote HSV-1 infection also interact with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 62 publications
1
36
0
Order By: Relevance
“…As HSV-1 coevolved with its human host, it is likely that some host factors, that are involved in viral replication, might be specific to human cells (Lou et al, 2016). To test if the number of viral genomes replicating per cell is cell type dependent, we have infected two human cells types: the HFF and U2OS cells (human osteosarcoma cell line).…”
Section: Resultsmentioning
confidence: 99%
“…As HSV-1 coevolved with its human host, it is likely that some host factors, that are involved in viral replication, might be specific to human cells (Lou et al, 2016). To test if the number of viral genomes replicating per cell is cell type dependent, we have infected two human cells types: the HFF and U2OS cells (human osteosarcoma cell line).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have extensively documented species-specific host factors in restricting HIV replication (Mariani et al, 2003; Stremlau et al, 2004). Recent work has also extended this theme into the cross-species restriction of flaviviruses, herpesviruses (Aguirre et al, 2012; Lou et al, 2016; Patel et al, 2012) and influenza virus (Long et al, 2016; Meyerson et al, 2017). These studies provide critical mechanistic insight into the barrier of cross-species transmission of viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Further, these proteins can usually be identified bioinformatically by a special evolutionary signature contained in their gene sequence (dN/dS > 1, indicating that natural selection is acting in favor of nonsynonymous substitutions, dN, relative to the baseline rate of synonymous substitutions, dS). Identifying this dN/dS > 1 signature in mammalian genes, in particular those important for virus biology, has proven itself to be a powerful shortcut in identifying host proteins that interact differently with viruses in one possible animal host versus another [32, 44,45,50,78,81,82,[85][86][87][88][89][90][91][92][93][94][95][96][97]. Predictions based off of the identification of host genes with dN/dS > 1 must still be tested in the lab, but this combined bioinformatic and experimental approach can ultimately allow us to identify dangerous animal viruses for which human blocks are few rather than many.…”
Section: Viral Mutations That Overcome Barrier Amentioning
confidence: 99%
“…But any cellular protein important to virus biology that has diverged significantly in protein sequence between the animal host and humans has the potential to act as a barrier to zoonosis. Other, unexpected types of host proteins have been identified that are important for viruses but that don't translate from one host species to the next, such as DNA repair proteins [91], nuclear pore proteins [50,107], RNA nucleases [90], and proteins involved with translation and post-translational modification [89,108].…”
Section: Viral Mutations That Overcome Barrier Amentioning
confidence: 99%